Effect of Rossby and Kelvin Waves on Intensification and Lifetime of Tropical Cyclones in the Western Pacific: Syaidi Abdilah, Novvria Sagita - Syaidi Abdilah Syaidi Abdilah; Novvria Sagita Novvria Sagita (Jurnal Fisika dan Aplikasinya, 2023)
Tropical cyclone is a meteorological phenomenon that occurs on the synoptic scale to the meso scale originating from tropical waters. Weather variability in the tropics can be affected by the Equatorial Planetary Wave (EPW). Identification of the active phase of the EPW wave is done by using a filter on the daily OLR anomaly data in the period of TC occurrence for 5 years which aims to determine the EPW wave in modulating the intensity and lifetime of the TC. The results showed that the EPW wave modulated the TC frequency by 92% of all cases for 5 years in the Western Pacific Ocean which tended to be modulated by the Rossby wave by 45%. While CCEWs modulate TC by 36%, and Kelvin waves modulate TC by 11%. 70% of TCs have lifetimes more than equal to the average indicating that EPW waves modulate TC lifetimes. The global circulation pattern in the study area during the period of occurrence of TC modulated by EPW waves within a period of 5 years shows a cyclonal pattern and maximum wind intensity of more than 40 knots in the 850 hPa layer which supports the formation of TC genesis in the study area.